Molecular detection of blaCTX-m_2 in Proteus mirabilis (World Journal of Experimental Biosciences, 2015)
From 152 different clinical samples collected from patients in Baghdad, 20 isolates of Proteus mirabilis were identified by bacteriological and biochemical assays and confirmed by vitek 2 identification system. It was found that 20 (66.6%) isolates were identified as P. mirabilis and 10 (33.3%) isolates were P. vulgaris. Susceptibility of P. mirabilis to cefotaxime was done, Notable, 13 (65%) P. mirabilis isolates were resistant to cefotaxime, whereas, 6 (30%) P. mirabilis isolates were extended spectrum beta-lactamases producers. MIC value of cefotaxime was estimated to 7 isolates (512 μg/ml), and the MIC was 4096 μg/ml for other isolates, One isolate had MIC equal to 128 μg/ml while, another isolate showed MIC equal to 8192 μg/ml to cefotaxime. DNA was extracted from 8 P. mirabilis isolates that was resistant to cefotaxime and 2 isolates were sensitive to cefotaxime. The blaCTX-M-2 gene was detected by polymerase chain reaction (PCR). The 8 cefotaxime resistant P. mirabilis isolates and one cefotaxime sensitive isolate carried blaCTX-M-2 gene, while the cefotaxime-sensitive isolate did not harbored the gene. Furthermore, this study confirmed that blaCTX-M-2 gene was carried on chromosomal DNA, by extraction the DNA from 10 P. mirabilis isolates having blaCTX-M-2 gene. DNA profile showed chromosomal DNA band only. Curing of blaCTX-M-2 gene was done, 4 cefotaxime-resistant P. mirabilis isolates were treated with ethidium bromide as a chemical curing agent in different concentrations. The results confirmed that blaCTX-M-2 gene was carried on chromosomal DNA.